Peningkatan Keaktifan Belajar Pada Pembelajaran Bahasa Indonesia Melalui Model Pembelajaran PBL, SMK Negeri 7 Semarang - Wahyu Nugroho; Nazla Maharani Umaya; Sri Kismiyati (Pascasarjana Universitas PGRI Semarang, 2025)
The aim of this study is to examine the effectiveness of implementing the Problem Based Learning (PBL) model in increasing student engagement in Indonesian language classes. Based on the research findings, it was discovered that the application of PBL significantly enhances students' active participation in the learning process. The collected data showed an increase in the percentage of active learning, from 30% in the Pre-Cycle stage, rising to 48% in Cycle 1, and reaching 72% in Cycle 2. This increase in engagement is reflected in various aspects, such as students' courage to ask questions to teachers and peers, the confidence to express opinions during presentations, and active participation in summarizing the lesson material. The 72% engagement rate surpasses the established success indicator of over 70%. These findings indicate that the PBL learning model is effective in enhancing students' active learning, making it a viable alternative learning strategy to improve the quality of education.